Brand Trust, Audience Engagement, and Interactivity as Determinants of Purchase Decisions in TikTok Live Commerce - Monalisa Monalisa; Astri Ayu Purwati; Ermina Rusilawati; Muhammad Firmansyah; Stanislaw Flejterski (International Journal of Information System and Innovation Management (IJISIM), 2025)
The rapid growth of live streaming commerce has transformed consumer purchasing behavior, particularly among Generation Z users of TikTok Live. This study aims to examine the effects of brand trust, audience engagement, and interactivity on purchase decisions among TikTok Live consumers in Pekanbaru City. A quantitative research design was employed, with data collected through a structured questionnaire from 120 respondents who had previously made purchases via TikTok Live. The data were analyzed using multiple linear regression to test the proposed hypotheses. The results indicate that brand trust and audience engagement have a positive and significant effect on purchase decisions. These findings suggest that consumers are more likely to make purchasing decisions when they trust the brand and actively engage with live streaming content. In contrast, interactivity was found to have a positive but insignificant effect on purchase decisions, indicating that interactive features alone do not directly drive purchasing behavior without the support of trust and engagement. Overall, the research model explains 61.4% of the variance in purchase decisions. This study contributes to the literature on live streaming commerce by highlighting the dominant roles of brand trust and audience engagement in shaping purchase decisions within the TikTok Live context. Practically, the findings provide insights for marketers and sellers to focus on trust-building strategies and engagement-driven content to enhance sales performance in live streaming environments.